Seven psychiatric traits and the risk of increased carotid intima-media thickness: a Mendelian randomization study - He, Kewan; Ying, Jiajun; Yang, Fangkun; Hu, Teng; Du, Yuewu (Frontiers in Cardiovascular Medicine, 2024)
Background: Numerous observational studies have suggested an association between psychiatric traits and carotid intima-media thickness (cIMT). However, whether these associations have a causal relationship remains unknown, largely due to issues of reverse causality and potential confounders. This study aims to elucidate the potential causal role of psychiatric traits in the risk of arterial injury as measured by cIMT. Methods: We utilized instrumental variables for attention deficit/hyperactivity disorder (ADHD, n=226,534), bipolar disorder (n=353,899), major depressive disorder (n=142,646), post-traumatic stress disorder (n=174,494), obsessive-compulsive disorder (n=9,725), autism spectrum disorder (n=173,773), and anxiety disease (n=17,310), derived from the largest corresponding genome-wide association studies (GWAS). Summary statistics for cIMT associations were obtained from a meta-analysis combining GWAS data from the Cohorts for Heart and Aging Research in Genomic Epidemiology consortia (n=71,128) and the UK Biobank study (n=45,185). The inverse-variance weighted method served as the primary analytical tool, supplemented by additional statistical methods in the secondary analyses to corroborate the findings. Adjustments were made according to the Bonferroni correction threshold. Results: The Mendelian randomization analyses indicated a suggestive causal link between genetically predicted ADHD and cIMT (beta=0.05; 95% confidence interval, 0.01-0.09; p=0.018). Sensitivity analyses largely concurred with this finding.However, no significant associations were found between other psychiatric traits and cIMT. Conclusions: This study provides insights into the risk effect of ADHD on cIMT, suggesting that arteriopathy and potential associated complications should be considered during the treatment and monitoring of patients with ADHD.